A study of the impact of strategic thinking on the performance of Mashhad municipal managers - Mahdi Mahdavian; Vahid Reza Mirabi; Farideh Haghshenas (Management Science Letters)
This examines the impact of strategic thinking on the performance of Mashhad municipal mangers. Strategic thinking as one of the ways of thinking has a crucial place in the modern world and plays essential role in major issues at different organizational levels including individual decision-making and planning. We expand our horizons and take the opportunity to increase our performance using strategic thinking. Organizations are being involved in competitive and chaotic situations; therefore, they need managers with strategic thinking. Nevertheless, there are some organizations throughout the world managing their business activities in increasingly difficult situations with highly developed duties. Therefore, they need strategic thinkers to cope up with the mentioned problems and Mashhad Municipality is no exception to this policy because it has a special place among all aspects of metropolitan districts. Thus, this study has attempted to explain of the impact of strategic thinking on the performance of Mashhad municipal managers. The results obtained from the study show that strategic thinking had an acceptable level among municipal managers of Mashhad City and all factors of strategic thinking improved their performance.